Persepsi Guru tentang Program Sertifikasi dalam Peningkatan Kompetensi Pedagogik di SDN Meruya Selatan 01 Pagi - Dwiana Paramita; Nurul Febrianti (Departement of Mathematics Education, 2023)
The goal to be achieved in this study is to teacher’s perceptions of the certification program in enhancement pedagogical competence at Meruya Selatan 01 Elementary School Am. The method used in this research is descriptive quantitative. The population in this study were all teachers at Meruya Selatan 01 Elementary School am, totaling 25 teachers. Sampling was carried out using saturated sampling technique, in which the entire population was used as a sample. The data collection technique uses closed questionnaires. Data analysis in this study was carried out in a simple quantitative descriptive manner using intervals and percentages. The results showed that the majority of teachers' perceptions of the certification program were very good, obtained from 16 (64%) teachers who answered. In the implementation of pedagogic competence, there were 7 (28%) teachers doing it quite well. This is a pretty good discovery in the school environment, because it means that the teacher certification program pursued by the government with the aim of increasing competency is going quite well or there are still results, although not optimal. However, it should also be noted that teachers who have very good perceptions of the certification program do not always have very good pedagogical competence. In fact, from the results of the study, it was found that there were more teachers whose pedagogical competence was only in the fairly good category. This is also a note for teachers to be more creative in improving their competence.